2020
DOI: 10.4251/wjgo.v12.i12.1381
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy reduces subsequent cholangiocarcinoma risk in choledocholithiasis patients undergoing endoscopic intervention

Abstract: BACKGROUND Cholangiocarcinoma is a disease with a high mortality rate. Our previous study revealed that cholelithiasis patients who undergo endoscopic sphincterotomy (ES)/endoscopic papillary balloon dilatation are at a higher risk for subsequent cholangiocarcinoma than cholelithiasis patients who undergo cholecystectomy. AIM To clarify the relationship between recurrent biliary events and subsequent cholangiocarcinoma risk in choledocholithiasis patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Biliary tract cancers, which can be divided into ICC, ECC, and AVC, are lethal diseases in the biliary system [ 20 ]. Our previous population-database cohort study showed that CCY was associated with a lower risk of cholangiocarcinoma in patients who underwent ERCP for bile duct stones management [ 21 ], but the evidence was not strong owing to the limited number of further cholangiocarcinoma cases. Therefore, we conducted a large-scale whole population-database cohort study in Taiwan and provided detailed confounding factor adjustments to clarify the association between CCY and the risk of pancreaticobiliary cancers after the ERCP management of choledocholithiasis and acute cholangitis.…”
Section: Introductionmentioning
confidence: 99%
“…Biliary tract cancers, which can be divided into ICC, ECC, and AVC, are lethal diseases in the biliary system [ 20 ]. Our previous population-database cohort study showed that CCY was associated with a lower risk of cholangiocarcinoma in patients who underwent ERCP for bile duct stones management [ 21 ], but the evidence was not strong owing to the limited number of further cholangiocarcinoma cases. Therefore, we conducted a large-scale whole population-database cohort study in Taiwan and provided detailed confounding factor adjustments to clarify the association between CCY and the risk of pancreaticobiliary cancers after the ERCP management of choledocholithiasis and acute cholangitis.…”
Section: Introductionmentioning
confidence: 99%